PENGARUH LATIHAN HARNESS DAN LATIHAN PARACHUTE TERHADAP HASIL LARI 60 METER PADA MAHASISWA KOP ATLETIK UNJ - Marlita Hayun; Agus Kurniadi (Jayabama: Jurnal Peminat Olahraga, 2024)
The purpose of this study is to find out: 1) The effect of Harness training on the results of the 60-meter run in UNJ Athletic KOP students, 2) The effect of Parachute training on the results of the 60-meter run in UNJ Athletics KOP students, 3) Comparison of Harness training and Parachute training on the results of the 60-meter run in UNJ Athletics KOP students. The research method used is an experiment with the "Pre-Test and Post-Test Two Group Design" design. The instrument used was a 60-meter running test. The population of this study is UNJ Athletic KOP students consisting of 25 students. Sampling was carried out randomly into two groups, 10 students each for the Harness training group and 10 students for the Parachute training group. Data analysis using t. The results of the analysis showed that there was a significant influence of Harness training on the improvement of 60-meter running results (t-count 7.601 > t-table 2.262).